Posterior reperfusion T-waves: Wellens' syndrome of the posterior wall. Issue 2 (29th July 2016) - Driver, Brian E; Shroff, Gautam R; Smith, Stephen W
Abstract : Background: Reperfusion after coronary occlusion (myocardial infarction, MI), as in Wellens' syndrome, is often represented on ECG as T-wave inversion in the leads overlying the affected myocardial wall(s). As an extension of this logic, reperfusion of the posterior wall should manifest on right precordial leads (which are opposite the posterior wall) as enlarged T-waves. Objective: We sought to determine whether T-wave amplitude (TWa) in leads V2 and V3 after reperfusion in posterior MI (PMI) is greater than in patients without PMI. Methods: Review of ECGs from patients with ST elevation MI of the left circumflex or right coronary artery with post-procedure thrombolysis in MI (TIMI) flow >0 between 2007 and 2009. Blinded experts reviewed admission ECGs to determine the presence of PMI and measure TWa before and after reperfusion. Maximum TWa in V2 and V3 and the difference between maximum and admission V2 and V3 TWa were compared between those with and without PMI. Results: Of 72 patients, 48 had PMI. Values expressed are medians and IQRs. Maximum TWa after reperfusion was greater in PMI than in non-PMI in V2 (5.00 mm (3.5 to 8.25) vs 3.9 mm (2.75 to 5.5), p=0.04), but not in V3 (4.0 mm (2 to 5.5) vs 3.0 mm (1.75 to 4), p=0.09). The increase in TWa in V2 and V3 after reperfusion was greater in PMI compared with non-PMI: (V2, 3.4 mm (2 to 5.25) vs 1.25 mm (−0.25 to 2), p=0.0005; V3, 2 mm (−0.5 to 3.25) vs 0.25 mm (−1 to 1.75), p=0.03). Conclusions: Reperfusion of the posterior wall results in higher right precordial TWa, and an even greater increase in TWa, as measured in leads V2 and V3. This observation has important implications for emergency physicians to accurately identify recent posterior infarction in patients who may be symptom free on presentation but at risk of reocclusion.